PENGARUH SELF MANAGEMENT TERHADAP TEKANAN DARAH LANSIA YANG MENGALAMI HIPERTENSI - Nur Isnaini; Inda Galuh Lestari (Universitas Muhammadiyah Ponorogo, 2018)
Elderly with hypertension having difficulty controlling blood pressure will worsen their health. Individuals with heart disease are advised to carry out self-management as one of the management of disease in everyday life. The purpose of this study is to determine the status of Self Management in Hypertension Elderly in Posbindu Dukuhturi-Bumiayu. This study uses descriptive analytic, crosssectional approach. Sample of 36 elderly with sampling technique nonprobabilitas sampling with type of accidental sampling. The research instrument used self management hypertension questionnaire which has been tested for validity and reliability. Data analysis using Spearman Rank test. Based on the research, it was found that most respondents had moderate self management that was 21 people (58.3%). There is a very significant positive influence between self management with blood pressure (systolic and diastolic). Spearman Rank test result from self management with systolic blood pressure got p value = 0.000 (a = 0,05) while result of self management with diastolic blood pressure got p value = 0,034 (a = 0,05).